Nilai-Nilai Pendidikan dalam Al-Qur’an dan Hadis: Analisis Tematik sebagai Dasar Pengembangan Kurikulum - Nurjana Cyntia Rahman; Muh. Arif (Chalim Journal of Teaching and Learning, 2025)
Islamic education plays a fundamental role in shaping human character and civilization based on divine values. However, contemporary educational practices often experience a reduction in meaning by overemphasizing cognitive achievement while neglecting spiritual and moral dimensions. This study aims to examine the educational values embedded in the Qur’an and Hadith as the foundation for character formation and civilizational development. Employing a qualitative approach with a library research method, this study conducts a thematic analysis of Qur’anic verses and Prophetic traditions related to Islamic education, referring to authoritative Qur’anic exegesis and Hadith commentaries. The findings reveal that the Qur’an emphasizes reading, critical thinking, and the pursuit of knowledge as integral forms of devotion to Allah, while the Hadith reinforce these principles through the obligation to seek knowledge and the enduring value of beneficial knowledge as a continuous act of worship. This study contributes to strengthening an integrative conceptual framework of Islamic education that remains relevant in addressing contemporary educational challenges.